Throwing Discretion to the Wind: Discretionary Denials in Instituting Inter Partes Review Under the NHK-Fintiv Framework - Douglas Crandell (Washington University Journal of Law and Policy, 2022)
In 2011, Congress passed the America Invents Act to reform the patent system and introduce new post-grant proceedings, such as inter partes review (IPR), for parties to challenge patent validity after the patent had been issued. For each petition for IPR, the United States Patent & Trademark Office Director retains authority, delegated to the Patent Trial and Appeals Board (“the Board”), to decide whether or not the petition should be instituted. Increasingly however, a significant number of petitions are being denied under 35 U.S.C. § 314(a) due to the status of parallel district court proceedings, rather than on the merits of the petition itself. This Note provides an overview of the history of post-grant proceedings prior to the Act and the motivation for replacing those proceedings with IPR. The author details the recent rise in decisions denying institution of IPRs for procedural reasons under § 314(a) and the factors the Board uses in making their determinations. The author advocates for changes to these factors and argues that the proposed changes would likely curb the dramatic rise of decisions denying IPRs on procedural grounds rather than their merits and better allow IPR to serve its intended function as an alternative to litigation.
Keywords: Patent; Congress; America; Invents; Act; Post-grant; Inter; Partes; Review; Challenge; Validity; Trademark; Trial; Appeals; Board; petiton; 314(a); Parallel; Proceedings; IPR; Procedural; Factual; Merits; Alternative; Litigation